Evaluation of Infraorbital Canal in Cone Beam Computed Tomography of Maxillary Sinus - Abdolaziz Haghnegahdar; Leila Khojastepour; Atefe Naderi (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Ignoring anatomic variations may lead to iatrogenic injuries by surgeons. Purpose: The aim of this study was to examine the relationship between the course of infraorbital canal and maxillary sinus using cone beam computed tomography scans (CBCT). Materials and Method: One hundred and ninety two CBCT scans were reviewed for 384 infraorbital canals. The anatomic variants of infraorbital canals were classified into three types based on the protrusion degree of the infraorbital nerve from the maxillary roof into the sinus. Measurements were made on infraorbital canal as vertical distance from the infraorbital rim to the infraorbital foramen, the maximum horizontal distance from the infraorbital canal to the canine root, the maximum diagonal length of the nerve protruded in sinus, the maximum vertical distance from the center of the nerve to the sinus roof. Results: 26.5% of infraorbital canals were entirely contained within the sinus roof. 50.3% of infraorbital canals were located below the roof but remaining juxtaposed to it. In 23.2%, the nerve canal descended into the sinus. The prevalence of type3 of infraorbital canal significantly increased from 14.8% in cases without an ipsilateral Haller cell to 29.1% when a Haller cell was present. The average distance between the infraorbital foramen and the infraorbital rim were increased proportionally to the degree of protrusion of the nerve course into the maxillary sinus (ANOVA p< 0.001). Conclusion: The infraorbital canal protrusion into the sinus is a common variation that must be considered during surgical procedures to avoid iatrogenic injury.